APPSNOGRAPHY: Observing the Practices of Using Digital Applications in Five Technocultural Aspects - Wijaya, Bambang Sukma (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2017)
The development of digital application technology has given rise to distinctive phenomena in using and consuming digital applications. User experiences can vary and even be unique. This article focuses on five aspects of observing naturally, authentically, and in detail regarding digital application use: techno-physical, techno-sociocultural, techno-discursive, techno-communicative, and techno-mediality. Apart from being a methodological reference for researchers, this article also provides valuable insights for designers and managers of digital applications. To cite this article (7th APA style): Wijaya, B. S. (2017). Appsnography: Observing the Practices of Using Digital Applications in Five Technocultural Aspects. Journal Communication Spectrum: Capturing New Perspectives in Communication 7(1), 74-83. https://doi.org/10.36782/jcs.v7i1.2366